2014
DOI: 10.1017/s1041610214002191
|View full text |Cite
|
Sign up to set email alerts
|

The state of psychogeriatrics in Europe: challenges and opportunities in six European countries

Abstract: With the increase in aging all over the world, and the elderly population nearly tripling from 524 million (8% of the world's population) in 2010 to 1.5 billion (16% of the world's population) in 2050, we will face new challenges and opportunities in providing healthcare. In 2050, it is estimated that Europe will see an increase of 70% in elderly population aged over 65 years, and 170% in those aged over 80 years (World Health Organization (WHO), 2011). It is vital to respond to the needs of this emerging popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Further, the findings reflect a global trend in healthcare provision towards an increase in the proportion of unqualified as opposed to qualified staff, and a relative increase in the presence of non‐medical as opposed to medically trained personnel. For comparison, it is noteworthy that Old Age Psychiatry as a specialty has been described as largely an Anglo‐Saxon phenomenon and in Europe services are highly variable . One report suggested that only the Netherlands, Switzerland, and the UK possessed a significant level of specialist provision…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the findings reflect a global trend in healthcare provision towards an increase in the proportion of unqualified as opposed to qualified staff, and a relative increase in the presence of non‐medical as opposed to medically trained personnel. For comparison, it is noteworthy that Old Age Psychiatry as a specialty has been described as largely an Anglo‐Saxon phenomenon and in Europe services are highly variable . One report suggested that only the Netherlands, Switzerland, and the UK possessed a significant level of specialist provision…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overall pattern of support provided to staff in mainstream settings (including primary care) was patchy, and many teams said they lacked the time and resources to provide the assistance required. Other jurisdictions have similarly demonstrated and advised the development of such links …”
Section: Discussionmentioning
confidence: 99%
“…Since old age mental health services availability does not follow the pattern of variation of the population of elderly people across the studied major socioeconomic regions, it becomes clear that the development of such services was not based on mapping or top-down planning of service provision. Such imbalances have been observed in geriatric mental health services in other European countries too [33], as well as in memory clinics [30]. Despite these imbalances and the international trends of developing specialized old age mental health care services [6,13,15], new psychogeriatric units in the studied region are being planned and inaugurated in a relatively slow rhythm.…”
Section: Discussionmentioning
confidence: 95%
“…Even though specific training in psychogeriatrics has been placed at the top of the list of priorities of the plans of action of psychogeriatric associations across the globe and was seen as top priority by many head physicians of psychogeriatric units in Southern Balkans [33,51], educational psychogeriatric programs in this part of Europe are still in their infancy. The undergraduate psychogeriatrics elective courses at the University of Varna and at the Aristotle University of Thessaloniki and the "Physiology of Aging and Geriatric Syndromes" postgraduate program at the National and Kapodistrian University of Athens embody three pioneer efforts.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Neste cenário, as respostas dos serviços são insuficientes. 16,17 Um diagnóstico mais precoce melhoraria os cuidados de muitos doentes e familiares. 18 Apesar das tentativas para implementar um diagnóstico atempado, persistem barreiras importantes, frequentemente por normalização dos sintomas ou falta de informação.…”
Section: Introductionunclassified